Infectious Mononucleosis - Schlossberg, David (Clinical topics in infectious disease., 1989)
Thoroughly revised and expanded, this comprehensive reference details all aspects of infectious mononucleosis. Initial chapters discuss the etiology, epidemiology, and pathogenesis of infectious mononucleosis. These are followed by chapters that thoroughly deal with the clinical presentation of the disease, including neurological and non-neurological manifestations and atypical presentations. Chapters on the hematologic response, the humoral response, and cell-mediated immunity describe the biological impact of the disease. The book concludes with reviews of diagnostic criteria and differential diagnosis, the pathology of the disease, and a new chapter on the chronic fatigue syndrome. From symptomatic infection to fatal lymphoproliferation, this book affords a fascinating study of infectious mononucleosis. Authoritative and up-to-date, it will prove a useful reference to all primary care physicians. Praise for the first edition: "(T)he book's size, easy readability of most chapters, and compilation of diverse topics make this monograph a valuable description of the diverse aspects of clinical disease caused by EBV." American Journal of Diseases of Children #1.